The state and development of science and technology parks in China - Enderwick, Peter (Henry Stewart Talks, 2013)
The importance of technology to China and its challenges, China's innovative potential & system, China's economic ambitions, China's technological performance, Research and development plans, costs, spending & staff, Comparison of R&D performance and R&D in OECD and non OECD economies, Student numbers and focus, Patents and trademarks per capita, University & Innovation 'hotspots', Patents, Basic research and High-tech exports, Criticisms of China's S&T parks, Foreign MNEs concerns with Chinese R&D staff